An analysis of citizens' jury on the Korean national pandemic response system - Lee, Young Hee (Javnost (Ljubljana), 2014)
Due to technical complexity, most public policies in technological society are dominated by expert-centrism and technocracy (an institutional form of expert-centrism), based on the belief that they should be the exclusive realm of technical experts. But globally, expert-led and technocratic policy-making culture is faced with challenges. We analyse the democratic implications of the Korean experience of the citizens' jury, a form of citizens' deliberative participation. We document and examine the citizens' jury on the National Pandemic Response System in 2008, which was the first case of the citizens' jury in Korea. We conclude that such characteristics of citizens' jury present positive implications in realising deliberative democracy.
Keywords: Južna Koreja; država; state; politics; politika; democracy; demokracija; državljani; komuniciranje; communication